What are the greatest opportunities for innovation to improve access to and quality of palliative care services to children? A qualitative interview study - K. Grailey; J. Roland; M. Lambert; G. Fontana; L. Dale-Harris; I. Williams; A. Shaw; A. L. Neves; J. Downing (BMC Palliative Care)
Abstract Background Innovation is required within children’s palliative care (CPC) to improve access to and quality of care. Existing research demonstrates a lack of access to CPC worldwide. This study aimed to explore the current opportunities for innovation within CPC from the provider’s perspective. Methods Global leaders in CPC were purposively sampled and invited to partake in a qualitative semi-structured interview. Data were thematically analysed using an inductive approach. Results Fifty-one CPC leaders from 27 countries were interviewed, encompassing clinical, managerial and patient advocacy roles. A thematic framework housing nine key themes was created, reflecting what innovation means in the context of CPC and the future of innovation. Key findings included opportunities to leverage new technologies within the sector. The importance of a clear vision and user-centred design were seen as crucial when innovating in CPC. Conclusions This study provides novel insights into opportunities for innovation in CPC, creating a thematic framework that brings together key themes and may help guide future innovation. We also highlight essential areas for innovation such as the use of technology. In the context of existing guidance for the delivery of CPC, leaders and policy makers can use the insights from this work to innovate and improve quality and access to CPC worldwide.